Pengaruh Transformational Leadership, HSE Program, Employee Engagement terhadap Safety Behavior pada Industri Kontruksi Migas dengan Safety Climate sebagai Variabel Mediasi - Syofyan Hardi Sabana; Abdul Haeba Ramli (Yayasan Literasi Sains Indonesia, 2026)
The purpose of this study is to identify the influence of Transformational Leadership, HSE Program, Employee Engagement, and Safety Climate on Safety Behavior. Research data from companies engaged in the oil and gas construction sector. This study uses a quantitative approach through sampling with Purposive Sampling by distributing questionnaires to 190 employees with 38 questions. The questionnaire was distributed in September - November 2025 with the condition that respondents have a work period of more than 5 years. The data analysis method used Structural Equation Model (SEM) using SmartPLS 4.0. The results of the study indicate that Transformational Leadership and HSE Program have a positive effect on Safety Climate, while Employee Engagement does not have a significant effect on Safety Climate. Transformational Leadership, HSE Program, Employee Engagement and Safety Climate are proven to have a positive effect on Safety Behavior. These findings indicate that leadership and safety programs play a more indirect role through the formation of Safety Climate, while changes in employee safety behavior are more influenced by collective perceptions of safety priorities and employee psychological attachment to the organization.